Multilayer brazing composite material and manufacturing method thereof

By designing multi-layer brazing composite materials in aluminum heat exchangers and using the reasonable composition of the core layer and the intermediate layer, the problem of difficult to meet the corrosion resistance and fatigue resistance during the lightweight process of aluminum heat exchangers is solved, and the high corrosion resistance, fatigue resistance and brazing performance of the material is improved, and the advantages of sustainable development are achieved.

CN119610806APending Publication Date: 2025-03-14GRANGES ALUMINUM SHANGHAI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311183777.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to meet the requirements of high corrosion resistance and thermal shock fatigue resistance in the lightweight process of aluminum heat exchangers, and Mg-containing long-life alloys have problems of toxicity and brazing defects during the brazing process.

Method used

By designing a multi-layer brazing composite material, the core layer and the intermediate layer are used to combine the core layer and the intermediate layer. The core layer contains appropriate amounts of Si, Cu, Mn, Mg and other elements, and the intermediate layer contains a lower content of Mg and an appropriate amount of Si, Cu, Mn and other elements to improve the corrosion resistance, fatigue resistance and brazing properties of the material.

Benefits of technology

It has achieved further lightweighting of aluminum heat exchangers, while ensuring their high corrosion resistance and fatigue resistance, reducing carbon emissions, and having the advantages of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610806A_ABST
    Figure CN119610806A_ABST
Patent Text Reader

Abstract

The invention relates to a multi-layer brazing composite material which comprises a core material layer, a brazing layer and a middle layer located between the core material layer and the brazing layer, and the alloy of the core material layer comprises, by weight, 0.4%-0.8% of Si, 0.4%-1.2% of Cu, 1.0%-2.0% of Mn, 0.1%-0.6% of Mg, smaller than or equal to 0.5% of Zn, smaller than or equal to 0.7% of Fe and Zirt; 0.15% by weight, Tilt; 0.15 wt%, Cr < lt >; 0.15% by weight, inevitable impurities each having a content of less than 0.05% by weight and a total content of less than 0.2% by weight, and a remainder of Al; the alloy of the middle layer comprises the following components in percentage by weight: 0.2-1.0% of Si, less than or equal to 0.2% of Cu, 1.0-2.0% of Mn, less than or equal to 0.1% of Mg, less than or equal to 2% of Zn, less than or equal to 0.7% of Fe and Zrlt; 0.15% by weight, Tilt; 0.15 wt%, Cr < lt >; 0.15% by weight, inevitable impurities each having a content of less than 0.05% by weight and a total content of less than 0.2% by weight, and a remainder of Al. The multi-layer brazing composite material has the advantages of being low in carbon, environmentally friendly, capable of being lightened, good in mechanical property and high in corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum brazing, in particular to a multilayer brazing composite material and a manufacturing method thereof. Background Art

[0002] Currently, the world produces about 100 million tons of aluminum each year, of which 35% comes from waste, but 40% of it becomes waste during the manufacturing process. For sustainable development, aluminum is a double-sided material. On the one hand, the low density of aluminum products and parts helps to reduce energy consumption; on the other hand, the production of aluminum from ore to metal is an energy-intensive greenhouse industry and one of the largest producers of greenhouse gases (GHG).

[0003] Aluminum is a recyclable material, and the energy consumption and emissions of recycled aluminum produced by remelting are only 5% of those of producing primary aluminum from bauxite. This means that the recycling of aluminum will fundamentally change the energy and emission status of the aluminum industry and move towards a more sustainable development path.

[0004] The lightweighting of aluminum heat exchangers is an important part of the lightweighting of automobiles. It not only reduces energy consumption and emissions during vehicle operation, but also reduces energy consumption and emissions during the production process by reducing the amount of aluminum used. A feasible way to lightweight aluminum heat exchangers is to reduce the thickness of the tube wall in the heat exchanger.

[0005] Generally, as the thickness of the tube wall decreases, the corrosion resistance and fatigue resistance of the heat exchanger will also decrease, which may affect the reliability of the heat exchanger. As a major component of the automotive thermal management system, the reliability of the brazed aluminum heat exchanger during use has an important impact on the safety of the vehicle, especially in battery-powered electric vehicles, where the reliability of the heat exchanger will significantly affect the safety of the electric vehicle.

[0006] Taking the radiator flat tube as an example, considering its external corrosion / internal corrosion performance and thermal cycle / thermal shock fatigue performance, for the same material, the rate at which the corrosion performance of the material decreases is usually much greater than the rate at which its thickness decreases. Taking the pitting corrosion of aluminum as an example, its perforation time is proportional to the cube of the thickness. From the fatigue curve of aluminum alloy, it can be found that due to the increase in stress caused by thinning, the rate of reduction of fatigue life in the low-cycle fatigue stage is also much higher than the rate of thinning.

[0007] In order to meet the requirements of high corrosion resistance and thermal shock fatigue resistance at the same time, high-strength and long-life alloys become the first choice. Due to the poisoning effect of Mg on F-Al-K flux, when the thickness of the aluminum tube is thicker, the use of long-life alloys without Mg can meet the requirements of thermal shock fatigue resistance. However, as the wall thickness of the aluminum tube decreases, in order to meet the reliability requirements, the requirements for the performance of the tube wall material (especially thermal shock fatigue performance) increase. Therefore, it is gradually transformed to the use of long-life alloys containing Mg.

[0008] The following problems may occur when using long-life alloys containing Mg: 1. Since long-life alloys can only use low Si (<0.1wt.%), they can only be produced using raw aluminum, and carbon emissions are relatively high. 2. Due to the thinning of the thickness, the diffusion of Mg to the surface increases during the brazing process, and the poisoning effect of Mg on the F-Al-K flux [Reference 1] leads to the generation of brazing defects or a decrease in yield. Increasing the amount of flux to eliminate the harmful effects of Mg will lead to excessive residual flux interacting with the coolant to produce precipitation and corrosion problems [Reference 2]. 3. Since the Si content of long-life Mg-containing alloys is very low, the aging effect is not significant, and the increase in Mg is limited by the brazing performance, leaving no room for further improvement of mechanical properties.

[0009] Document 1: Tadashi TAKEMOTO, Akira MATSUNAWA, Toshihiro SHIBUTAN, "Reaction and Brazeability of Magnesium containing Aluminum Alloys with Non-corrosive Flux," in JOURNAL of the JAPAN ELECTRIC WELDING SOCIETY, 1997, 15(2), 241-246

[0010] Document 2: C.Alverson, M.Ranger, and HJDeBaun, "The Effects of ResidualControlled Atmospheric Brazing Flux on Engine Coolants," in Global Testing of Extended Service Engine Coolants and Related Fluids, ed.E.Eaton (WestConshohocken, PA: ASTM International, 2014), 175-194 Summary of the invention

[0011] In order to overcome the above-mentioned problem of using Mg-containing long-life alloys and solve the defects of the prior art in that the corrosion and fatigue performances are reduced due to the lightweighting of aluminum heat exchangers, this application creatively proposes a material with high corrosion resistance and high fatigue resistance, which achieves high use strength through the reasonable design of the core material layer, and achieves excellent brazing performance and corrosion performance through the introduction of a reasonably designed intermediate layer. The composite material of this application achieves the advantages of lightweight, good mechanical properties and high corrosion resistance through the reasonable matching of the layers, especially the reasonable matching between the core material layer and the intermediate layer.

[0012] The composite material of the present application has excellent corrosion resistance and fatigue resistance even at a relatively low thickness. The aluminum alloy tube made from the material of the present invention can have the advantages of thin tube wall, high corrosion resistance and good mechanical properties. Compared with the prior art, the present application can further reduce the weight of the aluminum heat exchanger and ensure its good reliability.

[0013] In addition, due to the design of each layer of the composite material of the present application, especially the design of the core material layer, the composite material of the present application can be prepared by consuming a large amount of waste materials, which is conducive to further reducing carbon emissions and has sustainable advantages.

[0014] In one aspect, the present application relates to a multilayer brazing composite material, comprising: a core material layer, a brazing layer, and an intermediate layer located between the core material layer and the brazing layer, wherein the alloy of the core material layer comprises: Si 0.4-0.8 wt.%, preferably 0.4-0.75 wt.%, more preferably 0.4-0.7 wt.%, Cu 0.4-1.2 wt.%, preferably 0.5-1.1 wt.%, more preferably 0.6-1.0 wt.%, Mn 1.0-2.0 wt.%, preferably 1.2-1.8 wt.%, Mg 0.1-0.6 wt.%, preferably 0.15-0.55 wt.%, Zn≤0.5 wt.%, preferably ≤0.4 wt.%, more preferably ≤0.2 wt.%, Fe≤0.7 wt.%, Zr<0.15 wt.%, Ti<0.15 wt.%, Cr<0.15 wt.%, unavoidable impurities each containing less than 0.05 wt.% and a total content of less than 0.2 wt.%, and the balance Al; the alloy of the intermediate layer comprises: Si 0.2-1.0 wt.%, preferably 0.3-0.9 wt.%, more preferably 0.35-0.85 wt.%, Cu≤0.2 wt.%, Mn 1.0-2.0 wt.%, preferably 1.2-1.8 wt.%, Mg≤0.1 wt.%, preferably ≤0.05 wt.%, more preferably excluding Mg, Zn≤2 wt.%, preferably ≤1 wt.%, more preferably ≤0.5 wt.%, Fe≤0.7 wt.%, Zr<0.15 wt.%, Ti<0.15 wt.%, Cr<0.15 wt.%, unavoidable impurities each containing less than 0.05 wt.% and a total content of less than 0.2 wt.%, and the balance is Al.

[0015] In another aspect, the present application relates to an aluminum alloy tube made of the multi-layer brazing composite material of the present application.

[0016] In yet another aspect, the present application relates to a heat exchanger comprising the multi-layer brazing composite material of the present application.

[0017] On the other hand, the present application relates to a method for preparing the multi-layer brazing composite material of the present application, which includes the following steps: preparing a core layer alloy, an intermediate layer alloy, a brazing layer alloy and an optional waterproof layer alloy; heat treating the intermediate layer alloy and rolling it into a plate to obtain a plate-like intermediate layer alloy; optionally heat treating the core layer alloy; heat treating the brazing layer alloy and the optional waterproof layer alloy and rolling them into a plate to obtain a plate-like brazing layer alloy and an optional plate-like waterproof layer alloy; stacking the plate-like intermediate layer alloy, the core layer alloy, the plate-like brazing layer alloy and the optional plate-like waterproof layer alloy in sequence, and compounding them to obtain a composite; heat treating the composite and rolling it to a target thickness; and softening annealing. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 : Shows the glow spectrum test results of Comparative Example 2b and Example 4b.

[0019] Figure 2 : a) shows the metallographic microscope picture of the grain structure of the test material after the brazing simulation of Example 4b, b) shows the metallographic microscope picture of the grain structure of the test material after the brazing simulation of Example 4b.

[0020] Figure 3 : a) shows a metallographic microscope picture of the grain structure of the test material after brazing simulation of Comparative Example 4, b) shows a metallographic microscope picture of the particle structure of the test material after brazing simulation of Comparative Example 4.

[0021] Figure 4 : A metallographic microscope image showing the particle structure of Example 4b after SWAAT test for 30 days.

[0022] Figure 5 : A metallographic microscope picture of the particle structure of Comparative Example 4 after SWAAT test for 3 days is shown. DETAILED DESCRIPTION

[0023] General Definitions and Terminology

[0024] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the definitions provided herein shall prevail. Unless otherwise indicated, all percentages, parts, ratios, etc. are by weight.

[0026] When quantity, concentration or other value or parameter is given as range, preferred range or preferred upper limit and lower limit or specific value, it should be understood as specifically disclosing all ranges formed by paired values ​​from any upper limit range or preferred value and any lower limit range or preferred value, regardless of whether the range is disclosed separately. Unless otherwise stated, when numerical range is quoted herein, the range refers to including its endpoints and integers and fractions within all such ranges. The scope of the present invention is not limited to the specific numerical value quoted when defining the range. For example, "1-8" covers 1, 2, 3, 4, 5, 6, 7, 8 and any sub-range consisting of any two values ​​therein, such as 2-6, 3-5.

[0027] The terms "about" and "approximately" when used with a numerical variable generally refer to the value of that variable and all values ​​of that variable are within experimental error (e.g., within a 95% confidence interval for the mean) or within ±10% of the specified value, or a wider range.

[0028] The terms "comprises", "includes", "has", "contains" or "involves" and other variations thereof herein are inclusive or open-ended and do not exclude other unlisted elements or method steps. It will be understood by those skilled in the art that the above terms such as "comprising" encompass the meaning of "consisting of". The expression "consisting of" excludes any element, step or ingredient not specified. The expression "consisting essentially of" means that the scope is limited to the specified elements, steps or ingredients, plus the optional presence of elements, steps or ingredients that do not substantially affect the basic and novel features of the claimed subject matter. It will be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".

[0029] The term "selected from..." means that one or more elements in the group listed later are independently selected and may include combinations of two or more elements.

[0030] When values ​​or end-points of a range are described herein, it should be understood that the disclosure includes the specific value or end-point cited.

[0031] As used herein, the terms "one or more" or "at least one" refer to one, two, three, four, five, six, seven, eight, nine or more.

[0032] Unless otherwise specified, the terms "combination thereof" and "mixture thereof" refer to a multi-component mixture of the elements, such as a two-component mixture, a three-component mixture, a four-component mixture and the maximum possible multi-component mixture.

[0033] In addition, if the number of parts or components of the present invention is not indicated before, it means that there is no limit to the number of occurrences (or existence) of the parts or components. Therefore, it should be interpreted as including one or at least one, and the singular form of the parts or components also includes the plural form, unless the numerical value obviously represents the singular.

[0034] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes both occurring and not occurring of said event or circumstance.

[0035] The term "surface" as used herein refers to the contact surface between an object and the outside world, which usually has no thickness, such as the contact surface between a composite material and the outside world. Its shape usually depends on the shape of the object, for example, it can be a plane or a curved surface structure.

[0036] The term "surface layer" as used herein refers to a portion of an object within a certain distance from the surface of the object, which usually has a certain thickness. For example, in a composite material, a portion within a certain distance (such as within a few microns, within tens of microns, within hundreds of microns, etc.) from its surface and has a certain thickness. Its shape is usually related to the shape of the object, for example, it can be a flat plate or a curved strip.

[0037] The term "AA3XXX alloy" used herein is a common alloy name in the art well known to those skilled in the art, such as GB-T 3190-2016 Deformed Aluminum and Aluminum Alloy Chemical Composition. AA3XXX alloy is a series of alloys with aluminum and manganese as the main elements. The 3XXX alloy herein includes but is not limited to 3003 aluminum alloy (AA3003), 3004 aluminum alloy (AA3004), and 3005 aluminum alloy (AA3005).

[0038] The term "AA6XXX alloy" used herein is a common alloy name in the art well known to those skilled in the art, such as GB-T 3190-2016 Deformed Aluminum and Aluminum Alloy Chemical Composition. AA6XXX alloy is a series of alloys with aluminum, magnesium and silicon as main elements. The AA6XXX alloy herein includes but is not limited to 6060 aluminum alloy (AA6060) and 6063 aluminum alloy (AA6063).

[0039] The term "AA4XXX alloy" used herein is a common alloy name in the art well known to those skilled in the art, such as GB-T 3190-2016 Deformed Aluminum and Aluminum Alloy Chemical Composition. AA4XXX alloy is a series of alloys with aluminum and silicon as main elements. For example, the 4XXX alloys herein include but are not limited to 4343 aluminum alloy (AA4343, 4045 aluminum alloy (AA4045).

[0040] The term "composite ratio" used herein refers to the ratio of the thickness of each layer to the total thickness of the composite material. Taking the core material layer as an example, the composite ratio of the core material layer is the ratio of the thickness of the core material layer to the total thickness of the multi-layer brazing composite material.

[0041] Multilayer brazing composites

[0042] The invention relates to a multi-layer brazing composite material, which comprises a multi-layer brazing composite material comprising: a core material layer, a brazing layer and an intermediate layer located between the core material layer and the brazing layer.

[0043] The thickness of the multilayer brazing composite material is related to the number of layers, and the thickness of each layer needs to be considered for further adjustment. For lightweight considerations, the thickness of the multilayer brazing composite material of the present application can be 1 mm or less, preferably 0.4 mm or less, and more preferably 0.25 mm or less, for example, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, etc.

[0044] The multilayer brazing composite material can be processed in the form of a tube, a plate, etc. according to actual needs. In one embodiment, the multilayer brazing composite material can be processed into a tube, and the thickness of the multilayer brazing composite material is less than 0.4 mm, preferably less than 0.25 mm.

[0045] Core layer

[0046] The core material layer is one of the main structures of the multilayer brazed composite material, and its characteristics (such as hardness, strength, toughness, etc.) will affect the multilayer brazed composite material. The core material plays a supporting role and is also the main source of the material's strength after welding.

[0047] The thickness of the core material layer can be selected according to actual needs. Generally speaking, the composite ratio of the core material layer can be 60-80%, for example, 60%, 65%, 70%, 72.5%, 75%, 80%, etc., so that the final composite material can obtain suitable properties (such as strength, hardness, deformation resistance, etc.).

[0048] Herein, the alloy of the core material layer refers to the alloy material used to prepare the core material layer, and may also be referred to as the raw material of the core material layer, the raw material alloy of the core material layer, etc. It is understandable that, in the preparation process of the composite material, the diffusion of elements may occur due to factors such as heat treatment and equipment contact, which may lead to certain differences between the actual composition of the core material layer and the alloy composition of the core material layer. Under the usual preparation conditions in the field, starting from the alloy of the core material layer of the present application, the desired actual composition of the core material layer can be given, thereby ensuring that the composite material has excellent performance. In one embodiment, in the multi-layer brazing composite material obtained by the preparation method described below, the raw material of the core material layer is the core material layer alloy described in the present application, and the core material layer has the desired actual composition.

[0049] As the layer with a higher composite ratio in the composite material, the core material layer usually has a key influence on the performance of the composite material. Through the reasonable design of the core material layer, the properties of the multilayer brazing composite material, especially the corrosion resistance and mechanical properties, can be effectively improved and optimized.

[0050] The type and content of the elements in the core layer alloy are important factors affecting the performance of the core layer, because the type and content of the elements will affect the type and content of the compounds formed between the elements, thereby affecting the material properties.

[0051] In the prior art, the improvement process of the core alloy is as follows: First, an aluminum alloy with a lower Si content is used to ensure good corrosion resistance. Subsequently, in order to improve the strength of the material, an appropriate amount of Mg is added to the aluminum alloy with a lower Si content to meet the strength requirements. However, as the requirements for lightweight heat exchangers increase further and the material thickness continues to decrease, the strength of the obtained thin-walled tube cannot meet the use requirements. Therefore, an aluminum alloy material containing a combination of Mg, Si, and Mn can be used as the core material to further enhance the strength. However, as the Si content increases, the corrosion resistance of the material decreases, which also affects the reliability of the product.

[0052] The present application has conducted in-depth research on the above technical issues. The inventors have found that for an aluminum alloy material containing a combination of Mg, Si, and Mn as a core layer alloy, when the specific content of each element is further controlled to obtain a specific composition, the strength and corrosion resistance of the core layer can be effectively improved at the same time, thereby enabling the composite material and its products to meet the higher requirements for lightweight and reliability in current practical applications.

[0053] The Si element in the alloy of the core material layer will affect the corrosion resistance and strength of the core material layer. In the core material, maintaining a low Si content can improve the corrosion resistance of the material. Si can promote the precipitation of Mn from the solid solution to obtain a high-density dispersed particle phase of AlMnSi, thereby improving the strength of the composite material. If the Si content is too low, it will be unfavorable for improving the strength of the product. If the Si content is too high, the corrosion resistance will be significantly deteriorated. The alloy of the core material layer can contain 0.4-0.8% by weight, preferably 0.4-0.75% by weight, and more preferably 0.4-0.7% by weight of Si, for example 0.4% by weight, 0.5% by weight, 0.6% by weight, 0.7% by weight, 0.8% by weight, etc.

[0054] The inclusion of an appropriate amount of Mn in the core layer alloy helps to improve the strength, brazing properties, corrosion resistance and electrical potential of the material. When the Mn content is too low, the advantages it brings are not obvious; when the Mn content is too high, coarse Mn-containing particles will be formed, which will affect the rolling production and cause holes or broken strips to form in the material. The alloy of the core layer can contain 1.0-2.0% by weight, preferably 1.2-1.8% by weight of Mn, for example, 1.2% by weight, 1.3% by weight, 1.4% by weight, 1.5% by weight, 1.6% by weight, 1.7% by weight, 1.8% by weight, etc.

[0055] Cu can improve the strength of the core layer through solid solution strengthening and can increase the potential. If the Cu content in the core layer is too low, the advantages it brings are not obvious; if the Cu content is too high, the possibility of intergranular corrosion increases and the melting point may be significantly affected. The Cu content in the alloy of the core layer can be 0.4-1.2% by weight, preferably 0.5-1.1% by weight, and more preferably 0.6-1.0% by weight, for example, about 0.5% by weight, 0.6% by weight, 0.7% by weight, 0.8% by weight, 0.9% by weight, 1.0% by weight, etc.

[0056] The Mg element can significantly improve the strength of the alloy, and achieve the effect of improving strength through solid solution strengthening or through the precipitation of Mg2Si. When the Mg content is too low, its technical effect is weak. When the Mg content is too high, Mg may diffuse during the brazing process, which will have an adverse effect on the activity of the brazing agent, thereby causing the brazing effect to deteriorate; excessive Mg is also prone to intergranular corrosion. The Mg content in the alloy of the core layer can be 0.1-0.6% by weight, preferably 0.15-0.55% by weight, for example, 0.1% by weight, 0.2% by weight, 0.3% by weight, 0.4% by weight, 0.5% by weight, 0.6% by weight, etc.

[0057] The Fe element can be combined with other elements, such as Mn and Si, to form a casting crystalline phase. These crystalline phases can become intermetallic compounds of the size of recrystallization nuclei, which reduces the recrystallization temperature. The appropriate content of Fe can ensure that the material has good formability and corrosion resistance. The Fe content in the core layer alloy can be ≤0.7% by weight, for example, 0.05-0.7% by weight; for example, 0.05% by weight, 0.1% by weight, 0.25% by weight, 0.3% by weight, 0.4% by weight, 0.5% by weight, 0.6% by weight, 0.7% by weight, etc. Too high a Fe content may reduce the corrosion resistance of the composite material and also reduce the strength of the material.

[0058] Zn can affect the electrode potential of the core layer alloy, thereby affecting the corrosion performance. When the Zn content is too low, it is not conducive to the recycling of Zn-containing waste; when the Zn content is too high, the corrosion potential is too low, the potential difference between the core layer and the surface layer is reduced, and the corrosion performance deteriorates. The Zn content in the core layer alloy can be ≤0.4% by weight, more preferably ≤0.2% by weight, such as 0.05-0.4% by weight, such as 0.05% by weight, 0.1% by weight, 0.2% by weight, 0.4% by weight, etc.

[0059] Elements such as Zr, Ti, and Cr have a certain positive effect on adjusting strength and increasing corrosion resistance. The alloy in the core material can be added in an appropriate amount to adjust the performance. When Ti, Zr, and Cr are too high, huge intermetallic compounds are easily formed, which reduces plastic workability. The core layer alloy may contain <0.15 wt. % Zr. The core layer alloy may contain <0.15 wt. % Ti. The Cr content in the core layer alloy may be <0.15 wt. %.

[0060] The alloy of the core layer may contain: 0.4-0.8 wt. %, preferably 0.4-0.75 wt. %, more preferably 0.4-0.7 wt. % Si; 0.4-1.2 wt. %, preferably 0.5-1.1 wt. %, more preferably 0.6-1.0 wt. % Cu; 1.0-2.0 wt. %, preferably 1.2-1.8 wt. % Mn; 0.1-0.6 wt. %, preferably 0.15-0.55 wt. % Mg; ≤0.5 wt. %, preferably ≤0.4 wt. %, more preferably ≤0.2 wt. % Zn; ≤0.7 wt. % Fe; <0.15 wt. % Zr; <0.15 wt. % Ti; <0.15 wt. % Cr; unavoidable impurities each containing less than 0.05 wt. % and a total content of less than 0.2 wt. %; and the balance Al.

[0061] The alloy of the core material layer can be an alloy ingot formed by fusing various materials. Using waste as the raw material of the core material layer can improve the sustainable development efficiency of aluminum brazing materials and achieve a more green and environmentally friendly goal. The core material layer is the main part of the composite material, that is, the composite of the core material layer is relatively high, and the raw material of the core material layer contains a certain proportion of waste, which can significantly improve the recycling efficiency of the waste, which is of great significance to the goal of environmental protection. The composite material obtained by the design of the present invention still has excellent performance when there is a high content of Si and a high content of Mg in the core material layer alloy. Therefore, for the alloy of the core material layer, the use of pure aluminum ingots can be reduced. In other words, more waste can be consumed in the preparation process, and at the same time, the performance of the product can be guaranteed (for example, ensuring the reliability of the heat exchanger). In addition, for waste materials that are generally difficult to recycle, such as composite aluminum alloy waste, which may contain a high content of Si elements, Mg elements, etc., and the element composition is generally more complex than a single series of alloy waste (such as 3XXX, AA6XXX series alloys, etc.), because the core material layer alloy in the composite material of the present application can have a high Si and Mg content, so that such waste materials that are generally difficult to recycle can also be recycled.

[0062] In this article, waste can be post-consumer waste, process waste or a combination of the two. Process waste refers to: in the process of production and processing, due to the limited yield, a certain proportion of waste is inevitably generated, and this part of waste is called process waste. Post-consumer waste refers to: waste generated by the scrapping of aluminum alloy products (such as heat exchangers).

[0063] In one embodiment, the alloy of the core layer comprises more than 55 wt % of scrap, preferably more than 60 wt % of scrap, wherein the scrap comprises: AA3XXX series alloy scrap, AA6XXX series alloy scrap, composite aluminum alloy scrap or a combination thereof.

[0064] AA3XXX alloy scrap refers to scrap formed by one or more AA3XXX alloys. AA3XXX alloy scrap may contain: 0.5-0.7 wt% Si, 0.2-0.3 wt% Fe, 0.05-0.08 wt% Cu, 1.15-1.25 wt% Mn, <0.05 wt% Mg, <0.05 wt% Zn, <0.05 wt% Ti, the balance being Al and unavoidable impurities. In one embodiment, the AA3XXX alloy scrap used in the core layer alloy contains: 0.3 wt% Si, 0.7 wt% Fe, 0.08 wt% Cu, 1.25 wt% Mn, 0.01 wt% Mg, 0.01 wt% Zn, 0.02 wt% Ti, the balance being Al and unavoidable impurities.

[0065] AA6XXX alloy scrap refers to scrap formed by one or more AA6XXX alloys. AA3XXX alloy scrap may contain: 0.35-0.45 wt% Si, 0.15-0.2 wt% Fe, <0.05 wt% Cu, <0.05 wt% Mn, 0.45-0.55 wt% Mg, <0.05 wt% Zn, <0.05 wt% Ti, the balance being Al and unavoidable impurities. In one embodiment, the AA3XXX alloy scrap used in the core layer alloy contains: 0.45 wt% Si, 0.2 wt% Fe, 0.02 wt% Cu, 0.02 wt% Mn, 0.55 wt% Mg, 0.02 wt% Zn, 0.02 wt% Ti, the balance being Al and unavoidable impurities.

[0066] Composite aluminum alloy scrap refers to scrap formed by composite materials, so the composition is relatively more complex. In one embodiment, the composite aluminum alloy scrap used in the core layer alloy contains: 1.27 wt% Si, 0.24 wt% Fe, 0.4 wt% Cu, 1.18 wt% Mn, 0.01 wt% Mg, 0.14 wt% Zn, 0.09 wt% Ti, and the balance is Al and unavoidable impurities.

[0067] Middle Layer

[0068] The intermediate layer of the present invention is located between the core material layer and the brazing layer. The intermediate layer with suitable composition and thickness can achieve the effects of corrosion protection, melting protection, and prevention of diffusion of elements in the core material layer and the brazing layer (for example, Mg in the core material layer diffuses into the brazing layer, Si in the brazing layer diffuses into the core material layer, etc.).

[0069] The effects of the elements in the intermediate layer alloy are as described above. The intermediate layer contains a relatively low content of Mg, thereby preventing the diffusion of Mg in the core layer into the brazing layer, thereby avoiding the poisoning effect of Mg on the F-Al-K brazing flux. The Mg content of the intermediate layer is ≤0.1 wt%, preferably ≤0.05 wt%, and more preferably contains no Mg.

[0070] The alloy of the intermediate layer may contain: Si 0.2-1.0 wt.%, preferably 0.3-0.9 wt.%, more preferably 0.35-0.85 wt.%; Cu≤0.2 wt.%, Mn 1.0-2.0 wt.%, preferably 1.2-1.8 wt.%; Mg≤0.1 wt.%, preferably ≤0.05 wt.%, more preferably no Mg; Zn≤2 wt.%, preferably ≤1 wt.%, more preferably ≤0.5 wt.%; Fe≤0.7 wt.%; Zr<0.15 wt.%; Ti<0.15 wt.%; Cr<0.15 wt.%; unavoidable impurities each containing less than 0.05 wt.% and with a total content of less than 0.2 wt.%, and the balance Al.

[0071] The appropriate composite ratio of the middle layer helps to play the role of the middle layer. In one embodiment, the composite ratio of the middle layer is 5-25%, preferably 7.5-20%. If the composite ratio of the middle layer is too high, the strength of the composite material decreases; if the composite ratio of the middle layer is too low, it cannot effectively play its role.

[0072] Controlling the starting melting temperature of the core material layer and the middle layer can effectively prevent the core material from being melted during the brazing process. The starting melting temperature of the middle layer is more than 10°C higher than the starting melting temperature of the core material layer, which can prevent the melting of the core material during conventional brazing. Herein, "conventional brazing process" refers to the brazing process commonly used in the art. For example, the target temperature in the conventional brazing process can be about 595-605°C, and the specific parameters in the process can be appropriately adjusted according to the brazing environment, the parts to be welded, the brazing area, etc., to form a good quality brazed joint. The heating rate of the "conventional brazing process" from room temperature to 500°C is generally about 45-90°C / min, the heating rate of the 500-degree target temperature (595-600°C) is generally 12.5-25°C / Min, and the insulation time is generally 2-5min. Certain adjustments can be made according to the size of the heat exchanger and the brazing furnace.

[0073] The composition of the core layer and the intermediate layer will affect their respective starting melting temperatures. The core layer alloy and the intermediate layer alloy of the present application have suitable compositions so that the starting melting temperature of the intermediate layer is higher than the starting melting temperature of the core layer by more than 10°C.

[0074] The formation of grains of a certain size in the intermediate layer after brazing helps to improve the resistance to melting and corrosion, thereby improving the corrosion resistance. The average grain size of the intermediate layer after brazing can be above 100 μm, preferably above 120 μm. If the average grain size is too small, the intermediate layer cannot effectively prevent element diffusion and prevent the melting of molten solder, which may cause the core layer to melt, making the potential difference between the core material and the intermediate layer smaller, which may lead to a decrease in corrosion resistance. The average grain size of the intermediate layer after brazing can be controlled by regulating the chemical composition of the intermediate layer and controlling the production process of the intermediate layer (such as a heat treatment process).

[0075] Brazing layer and waterproof layer

[0076] In the multi-layer brazing composite material of the present invention, the brazing layer can cover the outer surface of the middle layer to give the composite material brazing properties.

[0077] The brazing layer may be an AA4XXX series alloy, such as AA4343, AA4045, etc. In one embodiment, the alloy of the brazing layer comprises: Si 5-14 wt%, preferably 6-13 wt%, more preferably 7-12.5 wt%; Fe≤0.7 wt%; Mg≤0.1 wt%, preferably≤0.05 wt%, more preferably no Mg; Cu≤0.1 wt%; Zn≤2 wt%, preferably≤1 wt%, more preferably≤0.5 wt%; Sr≤0.05 wt%; unavoidable impurities each having a content of less than 0.05 wt% and a total content of less than 0.2 wt%, and the balance of Al.

[0078] The thickness of the brazing layer will affect the brazing performance of the composite material. Too thin or too thick is not conducive to giving the composite material a good brazing effect. The composite ratio of the brazing layer can be 5-15%, for example 10%.

[0079] The composite material of the present application may also include a waterproof layer, which is located on the side of the core material layer away from the intermediate layer. The function of the waterproof layer is to prevent the core material from directly contacting the cooling medium and to prevent the moisture in the cooling medium from corroding the core material. In particular, when pure water is used as the cooling medium, the waterproof layer can effectively prevent the core material from being corroded.

[0080] The waterproof layer alloy of the present invention may contain Zn element. Zn has a sacrificial anode effect. Through the diffusion of Zn element, a corrosion potential gradient is formed, thereby reducing the corrosion risk from the cooling medium. The content of Zn in the waterproof layer may be 0.5-5% by weight.

[0081] When used in a heat exchanger, the brazing layer of the composite material of the present invention and the waterproof layer will be in direct contact during the brazing process, so the waterproof layer alloy does not contain Mg to avoid brazing failure. Herein, the alloy does not contain a specific element means that the element is not additionally added to the alloy raw material. For example, "the waterproof layer alloy does not contain Mg" means that Mg is not additionally added to the alloy used to prepare the waterproof layer.

[0082] The alloy of the waterproof layer may contain: Si 0.3-1.1 wt%, preferably 0.4-1.0 wt%, more preferably 0.45-0.95 wt%; Cu≤0.1 wt%; Mn 1.0-2.0 wt%, preferably 1.2-1.8 wt%; Zn≤5 wt%; Fe≤0.7 wt%; Mg≤0.03 wt%, more preferably excluding Mg; Zr<0.15 wt%; Ti<0.15 wt%; Cr<0.15 wt%; unavoidable impurities each containing less than 0.05 wt% and a total content of less than 0.2 wt%, and the balance Al.

[0083] For the composite material of the present application, it realizes further optimization of the performance of the material in the prior art. As mentioned above, the role of the elements in each layer is usually not single, because the elements are usually combined to produce unexpected results. The inventor unexpectedly found that the composite material of the present application (which has a specific structure, composition of each layer and microstructure) can have very good corrosion resistance and mechanical properties. Even when the thickness of the composite material is low (for example, less than 0.3mm), the corrosion resistance and high strength properties are also maintained. Products (such as heat exchangers) containing the composite material of the present application also have excellent corrosion resistance and mechanical properties, so high reliability can be obtained while meeting lightweight requirements.

[0084] When the total thickness of the multi-layer brazed composite material is 0.2 mm, the yield strength after brazing can be above 65 MPa, the tensile strength after brazing can be above 180 MPa, and the number of days for the first leakage to be discovered in the SWAAT test is above 8 days.

[0085] When the total thickness of the multi-layer brazed composite material is 0.25 mm, the yield strength after brazing can be above 70 MPa, the tensile strength after brazing can be above 185 MPa, and the number of days for the first leakage to be discovered in the SWAAT test is above 40 days.

[0086] In the present application, waste materials can be used to prepare the composite material of the present application, and the excellent performance of the composite material is maintained. In one embodiment, the alloy for preparing the multilayer brazing composite material contains more than 40% by weight of waste materials, wherein the waste materials include: AA3XXX alloy waste, AA6XXX alloy waste, composite aluminum alloy waste or a combination thereof. The waste content contained in the alloy for preparing the multilayer brazing composite material can also be referred to as the total waste consumption rate, that is, the weight of the added waste material accounts for the percentage of the total raw material weight in the process of preparing the multilayer brazing composite material.

[0087] Fabrication of multi-layer brazed composites

[0088] The present invention relates to a method for manufacturing the multilayer brazing composite material of the present invention, which comprises the following steps:

[0089] preparing a core layer alloy, an intermediate layer alloy, a brazing layer alloy and an optional waterproof layer alloy;

[0090] After heat treatment, the intermediate layer alloy is rolled into a plate to obtain a plate-shaped intermediate layer alloy;

[0091] optionally heat treating the core layer alloy;

[0092] After heat treatment, the brazing layer alloy and the optional waterproof layer alloy are rolled into a plate to obtain a plate-shaped brazing layer alloy and an optional plate-shaped waterproof layer alloy;

[0093] After stacking a plate-like intermediate layer alloy, a core material layer alloy, a plate-like brazing layer alloy, and an optional plate-like waterproof layer alloy in sequence, they are composited to obtain a composite body;

[0094] After heat treatment, the composite is rolled to a target thickness;

[0095] Softening annealing.

[0096] Suitable raw materials are selected to prepare the core layer alloy, the intermediate layer alloy, the brazing layer alloy and the optional waterproof layer alloy having the above-mentioned compositions. During the preparation of the alloy for the core layer, a certain proportion of waste materials may be added.

[0097] The heat treatment process helps to form the desired microstructure in the layer. After the intermediate layer alloy is heat treated, it is rolled into a plate to obtain a plate-shaped intermediate layer alloy. Through appropriate heat treatment, the average grain size and element segregation in the intermediate layer alloy can be controlled, thereby affecting its average grain size after brazing. The temperature of the heat treatment of the intermediate layer alloy can be 450-550°C.

[0098] The alloys of the individual layers can be processed by relevant processes (eg sawing, milling).

[0099] After stacking the plate-shaped intermediate layer alloy, the core material layer alloy and the plate-shaped brazing layer alloy in sequence, they are compounded to obtain a composite body. It is understood by those skilled in the art that the stacking sequence can be designed according to the desired composite material. The relative position relationship of each plate-shaped alloy in the composite body is the same as the relative position relationship of the composite material finally obtained.

[0100] The composite is rolled to a target thickness. The rolling method may include hot rolling, cold rolling and a combination thereof. In one embodiment, a hot-rolled coil is rolled by multiple hot rolling passes, and the hot-rolled coil is further cold-rolled to the final finished product thickness. The total reduction of the hot-rolled coil is at least 70%, preferably 80% or more. During the cold rolling process, an intermediate annealing treatment may be performed. In one embodiment, an intermediate annealing treatment below 380°C is performed during the cold rolling process.

[0101] The obtained composite body of the final finished product thickness is subjected to soft annealing. Soft annealing can improve and reduce rolling oil residue, eliminate internal stress and reduce strength, and prevent cracking during subsequent processing. The temperature of soft annealing can be reasonably selected according to the specific composition of the aluminum alloy composite material for brazing. However, it should be lower than the melting temperature of the brazing material contained in the aluminum alloy composite material for brazing to avoid melting of the brazing material during soft annealing. In one embodiment, the temperature of soft annealing is 200°C-300°C.

[0102] The preparation method of the present invention can give the composite material the desired structure (multilayer structure, microscopic particle state) and material properties. The obtained composite material has high strength, excellent corrosion resistance, and can consume more waste materials, and is particularly suitable for making pipes for various heat exchangers with low carbon requirements.

[0103] The present invention also relates to an aluminum alloy tube, which is made by the multi-layer brazing composite material of the present invention.

[0104] The present invention also relates to a heat exchanger, which comprises the multilayer brazing composite material of the present invention. The waterproof layer can be located on the liquid medium side, and the liquid medium includes but is not limited to heat exchanger coolant, pure water, etc.

[0105] Beneficial Effects

[0106] Since the premise of obtaining long-life alloys is to have a low Si content (Si<0.1wt%), only primary aluminum can be used for production, and carbon emissions are relatively high. In addition, due to the thinning of the thickness, the diffusion of Mg to the surface during brazing increases, and the poisoning effect of Mg on the F-Al-K flux leads to the generation of brazing defects or a decrease in yield. Increasing the amount of flux to eliminate the harmful effects of Mg will lead to excessive residual flux interacting with the coolant to produce precipitation and corrosion problems. The aging effect mainly depends on the formation of metastable strengthening phases of Mg2Si and Al-Mg-Cu-Si to strengthen the alloy. Since the Si content in the long-life Mg-containing alloy is very low, the metastable strengthening phase cannot be formed, so the aging effect is not significant, and the increase in Mg is limited by the brazing performance, and there is no room for further improvement of mechanical properties.

[0107] In order to solve these problems, the present invention realizes high use strength by rationally designing the core material layer, and realizes excellent brazing performance and corrosion resistance by introducing a rationally designed intermediate layer. The composite material of the present invention achieves the advantages of light weight, good mechanical properties and high corrosion resistance by rationally matching the layers, especially the core material layer and the intermediate layer.

[0108] Due to the design of each layer of the composite material of the present application, the composite material of the present application can be prepared by consuming a large amount of waste materials, which is conducive to further reducing carbon emissions and has sustainable advantages.

[0109] The composite material of the present application has very good corrosion resistance and excellent mechanical properties even at a relatively low thickness. The aluminum alloy tube made by the material of the present invention can have the advantages of thin tube wall, high corrosion resistance and high fatigue resistance. Compared with the prior art, the present application can further reduce the weight of the aluminum heat exchanger and ensure its good reliability.

[0110] Example

[0111] The solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0112] It should be noted that the following examples are merely examples for clearly illustrating the technical solutions of the present invention, and are not intended to limit the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description, and it is not necessary and impossible to exhaustively list all the embodiments here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention. Unless otherwise specified, the instruments, equipment, and reagents used herein are all commercially available.

[0113] The compositions of the prepared multilayer brazing composite materials are shown in Table 1.

[0114] The samples of the embodiments and comparative examples of the present invention were prepared according to the following method:

[0115] The core material layer alloy, the intermediate layer alloy, the brazing layer alloy and the waterproof layer alloy with specific compositions are melted and cast respectively, wherein a certain amount of waste is added during the preparation of the intermediate layer alloy, the core material layer alloy and / or the waterproof side alloy;

[0116] The intermediate layer alloy is heat treated at a temperature of 450-550° C. and then hot rolled to form a plate-shaped intermediate layer alloy;

[0117] The brazing layer alloy is rolled into a plate-shaped brazing layer alloy, and then the core alloy ingot and each layer of the plate-shaped alloy are combined and loaded into a heating furnace for heating, and then the combined material is hot-rolled for multiple passes at 500-300° C. to be rolled into a 4 mm thick hot-rolled coil;

[0118] The hot rolled coil is further cold rolled to the finished thickness. The composite material of the finished thickness is annealed at 200-300° C. to obtain the composite materials of the embodiments and comparative examples.

[0119] The structures and components of each layer of the embodiment and comparative example are shown in Tables 1 and 2 below:

[0120] Table 1

[0121]

[0122] Solidus temperature*: corresponds to the temperature at which an alloy begins to melt; liquidus temperature # : corresponds to the temperature at which the alloy is completely melted.

[0123] Table 2

[0124]

[0125]

[0126] Table 3

[0127]

[0128] Table 4

[0129]

[0130] Table 5

[0131]

[0132] Table 3 shows the nominal composition of the waste added in the preparation of the core material layer alloy. Table 4 shows the waste consumption in the process of preparing the composite materials of each embodiment and comparative example, wherein the total waste consumption rate indicates the ratio of the total weight of the waste added in the production process of the composite material to the total feed amount in the production process of the composite material. Table 5 shows the waste consumption in the process of preparing the core material layer of each embodiment and comparative example, wherein the waste consumption rate of the core material indicates the ratio of the total weight of the waste added in the production process of the core material to the total feed amount in the production process of the core material, that is, the percentage of waste in the alloy of the core material layer.

[0133] Experimental example

[0134] The composite materials of the examples and comparative examples were subjected to brazing simulation: the temperature was raised from room temperature to 500°C at a rate of 60°C / min, and from 500°C to 600°C at a rate of 15°C / min, and the temperature was kept at that temperature for 3 minutes, and then cooled under nitrogen for 10 minutes and then air-cooled to obtain the test materials after brazing simulation of the examples and comparative examples. Then, each test material was evaluated according to the following method.

[0135] GD-OES (Glow Spectroscopy) Test

[0136] Instrument: GDA750 (supplier: SPECTRΜMA).

[0137] Testing standards: ISO / TS25138ISO14707.

[0138] The brazing layer of the test material after brazing simulation was heated to 570°C (the temperature was raised from room temperature to 500°C at a rate of 60°C / min, and then from 500°C to 570°C at a rate of 15°C / min, and then taken out) was subjected to GD-OES test. The Mg content of the surface layer of the brazing layer of the test material after brazing simulation in the embodiment of the present application was kept in a relatively low range, and good brazing quality could be achieved. The results of the composite materials of Comparative Example 2b and Example 4b are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that, compared with the comparative example 2b, the Mg content of the surface layer of the brazing layer of the composite material of Example 4b is maintained in a lower range.

[0139] In Example 4b, the Mg content within 40 μm from the surface of the brazing layer was less than 0.05 wt %.

[0140] Determination of average grain size

[0141] The average grain size of the middle layer can be measured by a metallographic microscope and related software Image Pro. The grain size measurement is measured according to the intercept method of ASTM-E112.

[0142] The testing instruments and testing conditions for the grain structure metallographic micrographs are as follows:

[0143] Instrument: Ziess upright metallographic microscope. Detection conditions: The sample is mounted, ground and polished. Use 0.5% HF + 0.5% HBF4 aqueous solution, anodic coating for 1-2 minutes at 30-50V voltage, clean, blow dry, then flatten, place on the microscope, observe and take pictures in polarized light mode.

[0144] The testing instruments and testing conditions of the particle structure metallographic micrographs are as follows:

[0145] Instrument: Ziess upright metallographic microscope. Inspection conditions: The sample is mounted, ground and polished. Etched with 0.5% HF aqueous solution for 10-20 seconds, cleaned, blown dry, and then flattened, placed under a microscope for observation and photography in normal optical mode.

[0146] Figure 2 a is a metallographic microscope image showing the grain structure of the test material after brazing simulation of Example 4b, Figure 2 b shows a metallographic microscope picture of the particle structure of the test material after the brazing simulation of Example 4b.

[0147] Figure 3 a shows a metallographic microscope picture of the grain structure of the test material after brazing simulation of Comparative Example 4, Figure 3 b shows a metallographic microscope picture of the particle structure of the test material after brazing simulation of Comparative Example 4.

[0148] In the composite materials of the examples of the present application, the average grain size of the intermediate layer is above 100 μm. The specific results of the average grain size of the intermediate layer of Examples 4a-4b and Comparative Example 4 are shown in Table 7 below.

[0149] Mechanical properties test

[0150] The test materials after brazing simulation were prepared into tensile test specimens according to EN10002-1 standard, with a gauge length of 50 mm, and the tensile test was carried out at room temperature at a tensile speed of 20 mm / min.

[0151] The test materials after brazing simulation in the embodiments of the present application all have high yield strength and tensile strength and excellent mechanical properties. The following Table 6 shows the specific mechanical property test results of Comparative Examples 1-2, Comparative Example 4 and Examples 4a-4b. As can be seen from Table 6, the mechanical properties of the samples of Examples 4a-4b are better than those of Comparative Examples 1-2 and Comparative Examples 4-5.

[0152] The average grain size of the middle layer of the sample of Comparative Example 4 is too small, and its mechanical properties are significantly deteriorated compared with those of Examples 4a-4b.

[0153] Table 6

[0154]

[0155] After brazing*: It means that the mechanical properties test is carried out directly after the brazing simulation is completed, usually within about 12 hours after the brazing simulation is completed.

[0156] External corrosion test (SWAAT test)

[0157] The test material after brazing simulation was subjected to an experiment according to ASTM G85 (A3) to measure the time it takes for the material to corrode and perforate.

[0158] The days to first discovery of corrosion perforation (i.e., days to first discovery of leakage) of the test materials after brazing simulation in the examples of the present application are all relatively long, indicating that they have excellent corrosion resistance. The following Table 7 shows the SWAAT test results of the relevant comparative examples and examples.

[0159] Table 7

[0160]

[0161] The morphology of the sample after SWAAT test was observed by metallographic microscope. The metallographic microscope instrument was Ziess upright metallographic microscope. The detection conditions were as follows: the sample was mounted, polished, etched with 0.5% HF aqueous solution for 10-20 seconds, cleaned, blown dry, and then flattened and placed under a microscope for observation and photography.

[0162] Figure 4 The metallographic microscope picture of Example 4b after SWAAT test for 30 days is shown. Figure 5 The metallographic microscope image of Comparative Example 4 after SWAAT test for 3 days is shown. Figure 4 From the corrosion morphology of Example 4b, it can be seen that the corrosion develops along the surface of the composite material, and no perforation or leakage occurs. Figure 5 From the corrosion morphology of comparative example 4, it can be seen that local severe corrosion perforation occurred.

[0163] The technical content and technical features of the present disclosure have been disclosed above. However, it can be understood that under the creative ideas of the present disclosure, technicians in this field can make various changes and improvements to the above disclosed concepts, but they belong to the protection scope of the present disclosure. The description of the above implementation mode is exemplary rather than restrictive, and the protection scope of the present disclosure is determined by the claims.

Claims

1. A multilayer brazing composite material, comprising: Core material layer, Brazing layer, and an intermediate layer, which is located between the core material layer and the brazing layer, in, The alloy of the core material layer comprises: Si 0.4-0.8 wt%, preferably 0.4-0.75 wt%, more preferably 0.4-0.7 wt%, Cu 0.4-1.2 wt%, preferably 0.5-1.1 wt%, more preferably 0.6-1.0 wt%, Mn 1.0-2.0 wt%, preferably 1.2-1.8 wt%, Mg 0.1-0.6 wt%, preferably 0.15-0.55 wt%, Zn≤0.5 wt%, preferably ≤0.4 wt%, more preferably ≤0.2 wt%, Fe≤0.7wt%, Zr<0.15 wt%, Ti<0.15 wt%, Cr<0.15wt%, Unavoidable impurities each containing less than 0.05 wt% and less than 0.2 wt% in total, and the balance being Al; The alloy of the intermediate layer comprises: Si 0.2-1.0 wt%, preferably 0.3-0.9 wt%, more preferably 0.35-0.85 wt%, Cu ≤ 0.2 wt%, Mn 1.0-2.0 wt%, preferably 1.2-1.8 wt%, Mg≤0.1 wt%, preferably ≤0.05 wt%, more preferably no Mg, Zn≤2 wt%, preferably ≤1 wt%, more preferably ≤0.5 wt%, Fe≤0.7wt%, Zr<0.15 wt%, Ti<0.15 wt%, Cr<0.15wt%, Unavoidable impurities each containing less than 0.05 wt% and less than 0.2 wt% in total, and the balance being Al.

2. The multilayer brazing composite material according to claim 1, wherein: The melting start temperature of the intermediate layer is higher than the melting start temperature of the core layer by 10° C. or more.

3. The multilayer brazing composite material according to claim 1 or 2, wherein: The average grain size of the intermediate layer after brazing is greater than 100 μm, preferably greater than 120 μm.

4. The multilayer brazing composite material according to any one of claims 1 to 3, wherein: The alloy for preparing the multilayer brazing composite material contains more than 40% by weight of waste materials, wherein: The waste materials include: AA3XXX alloy waste materials, AA6XXX alloy waste materials, composite aluminum alloy waste materials or a combination thereof.

5. The multilayer brazing composite material according to any one of claims 1 to 4, wherein: The alloy of the core layer contains more than 55% by weight of scrap, wherein The waste materials include: AA3XXX alloy waste materials, AA6XXX alloy waste materials, composite aluminum alloy waste materials or a combination thereof.

6. The multilayer brazing composite material according to any one of claims 1 to 5, wherein: The composite ratio of the intermediate layer is 5-25%, preferably 7.5-20%.

7. The multilayer brazing composite material according to any one of claims 1 to 6, wherein: The alloy of the brazing layer is AA4XXX series alloy, Preferably, The alloy of the brazing layer comprises: Si 5-14 wt%, preferably 6-13 wt%, more preferably 7-12.5 wt%, Fe≤0.7wt%, Mg≤0.03% by weight, more preferably no Mg, Cu≤0.1wt%, Zn≤2 wt%, preferably ≤1 wt%, more preferably ≤0.5 wt%, Sr≤0.05wt%, Unavoidable impurities in an individual content of less than 0.05 wt. % and a total content of less than 0.2 wt. %, and The balance is Al.

8. The multilayer brazing composite material according to any one of claims 1 to 6, further comprising: A waterproof layer, which is located on a side of the core material layer away from the middle layer; The alloy of the waterproof layer comprises: Si 0.3-1.1 wt %, preferably 0.4-1.0 wt %, more preferably 0.45-0.95 wt %, Cu≤0.1wt%, Mn 1.0-2.0 wt%, preferably 1.2-1.8 wt% Zn≤5% by weight Fe≤0.7wt%, Mg≤0.1 wt%, preferably ≤0.05 wt%, more preferably no Mg, Zr<0.15 wt%, Ti<0.15 wt%, Cr<0.15wt%, Unavoidable impurities in an individual content of less than 0.05 wt. % and a total content of less than 0.2 wt. %, and The balance is Al.

9. The multilayer brazing composite material according to any one of claims 1 to 8, wherein: When the total thickness of the multi-layer brazing composite material is 0.2 mm, The multi-layer brazed composite material has a post-brazing yield strength of 65 MPa or more and / or a post-brazing tensile strength of 180 MPa or more, and / or the number of days after the multi-layer brazed composite material is first discovered to leak in a SWAAT test is more than 8 days.

10. The multilayer brazing composite material according to any one of claims 1 to 8, wherein: When the total thickness of the multi-layer brazing composite material is 0.25 mm, The multi-layer brazed composite material has a post-brazing yield strength of 70 MPa or more and / or a post-brazing tensile strength of 185 MPa or more, and / or the number of days after the multi-layer brazed composite material is first discovered to leak in a SWAAT test is more than 40 days.

11. An aluminum alloy tube made of the multi-layer brazing composite material according to any one of claims 1 to 10.

12. A heat exchanger comprising the multilayer brazing composite material according to any one of 1 to 10.

13. A method for preparing the multilayer brazing composite material according to any one of claims 1 to 10, comprising the following steps: preparing a core layer alloy, an intermediate layer alloy, a brazing layer alloy and an optional waterproof layer alloy; After heat treatment, the intermediate layer alloy is rolled into a plate to obtain a plate-shaped intermediate layer alloy; optionally heat treating the core layer alloy; Heat-treating the brazing layer alloy and the optional waterproof layer alloy and rolling them into a plate to obtain a plate-shaped brazing layer alloy and an optional plate-shaped waterproof layer alloy; After stacking a plate-like intermediate layer alloy, a core material layer alloy, a plate-like brazing layer alloy, and an optional plate-like waterproof layer alloy in sequence, they are composited to obtain a composite body; The composite body is heat treated and then rolled to a target thickness; and soft annealed.

Citation Information

Patent Citations

  • Multilayer braze-able sheet

    CN101443188A

  • Aluminum alloy composite material, heat exchanger tube and automobile

    CN111391430A

  • Five-layer aluminum alloy composite material and manufacturing method thereof

    CN113878947A

  • Aluminum alloy composite material for brazing and manufacturing method thereof

    CN115771311A

  • Brazing sheet by aluminum alloy for heat exchanger and method for production thereof

    JP2021021113A